APPROPRIATE USE OF IMAGING FOR DIAGNOSING LOW BACK PAIN IN PATIENTS PRESENTING TO THE EMERGENCY DEPARTMENT - MAZHAR, H; SUBHAN , U; AKRAM, MH (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in Shifa Hospital from January 2022 to January 2023 to assess the use of lumbar imaging in patients presenting to the emergency department for lower back pain. Participants' data, including case history, triage notes, imaging requests, and imaging results, were recorded. Decisions based on the clinician's clinical judgment and the American College of Physicians' guidelines were used to calculate the prevalence of underuse and overuse of lumbar imaging. (Rotondi and Donner, 2012). Kappa ≥0.5 indicated moderate inter-observer agreement and was considered acceptable. Data from 550 patients were reviewed. Results showed that 137 (24.9%) were referred for lumbar imaging and were older than those not. Of 550 cases, 44 (8%) were overused of images, and 22 (4%) of underuse. Many patients visiting the emergency department for low back pain are subjected to inappropriate lumbar imaging decisions.